Relationships between the level of strength of the upper and lower limbs and indicators of technical-tactical preparation of kickboxing fighters in the K1 formula competitions - Niewczas, M.; Rydzik, L.; Wasacz, W.; Ružbarský, P.; Ambrozy, T.; Król, P.; Dreher, P.; Spieszny, M. (Archives of Budo, 2023)
Background and Study Aim: Strength training is often considered a key element in preparing athletes for combat sports, as it allows them to increase their power capabilities and, through the interaction of motor skills, affects endurance and speed. The purpose of this study it was broaden knowledge about the level of strength of the upper and lower limbs of kickboxing competitors fighting in the K1 formula and to determine its impact on the level of technical-tactical training.